BIOPHYSICAL MODELING OF ELECTRICAL SIGNAL PROPAGATION IN NEURONAL MEMBRANES USING COMPUTATIONAL SIMULATION (Eureka Journal of Health Sciences & Medical Innovation, 2026)
The transmission of electrical signals in neurons is governed by complex biophysical mechanisms involving membrane ion channels, electrical gradients, and time-dependent changes in membrane potential. Understanding these processes is essential for advancing both theoretical neurobiophysics and applied biomedical research.
Keywords: Biophysics; Neuronal membrane; Electrical signal propagation; Action potential; Ion channels; Computational simulation